Interaction effect of cracks on flutter and divergence instabilities of cracked beams under subtangential forces. (January 2016) - Viola, Erasmo; Marzani, Alessandro; Fantuzzi, Nicholas
Highlights: The dynamic behaviour of double cracked beams is modelled using finite elements. Cracks interaction effect on flutter and divergence stabilities is investigated. The proposed procedure can tackle multi-cracked beams under subtangential loadings. Abstract: The dynamic stability of cracked beams under conservative and non-conservative forces and for various boundary conditions is investigated. In order to extend the formulation of a previous paper by the first two authors, here doubly cracked Euler–Bernoulli beams subjected to triangularly distributed subtangential forces are considered. Cracked sections are modelled through the theory of fracture mechanics and involve a line-spring stiffness matrix. The finite element method (FEM) is used to perform numerical computations. The stability maps, obtained from the eigenvalue analysis, define the divergence and flutter domains. The proposed procedure can also tackle general multi-cracked beams.